The changing role of primary health care in Malaysia - The past and the future - Yadav, Hematram; Ghani, Sirajoon Noor (Faculty of Medicine, University of Malaya, 2001)
The concept of primary health care (PHC) according to WHO has been implemented in Malaysia since 1978. The rural health centres which provide the primaryhealth care have developed from about 47 in 1970 to about 772 in 1998. Since the implementation of the health centres there has been significant reduction in morbidity and mortality rates. However due to the emerging issues like changing demographic 'patterns,changing pettern of disease, and increasing demand from the public, the delivery of PHC is being reviewed. Newer programmes and review of the older programmes are being done to address the provision of PHC in the 21st century. The functions and role of the existing staff in the health centres are being reviews. This new concept is known as expanded scope of primary health care. the purpose of this paper is to explain the achievements in primary health care and the components of primary health care in the expanded scope